Pentingnya Motivasi Dan Disiplin Kerja dalam Meningkatkan Kinerja Pegawai Pada Dinas Pertanian Kabupaten Kepulauan Aru - Juliams Siwalette; Nugrawan Saharuddin (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the impact of motivation and work discipline on employee performance at the Department of Agriculture of the Aru Islands Regency. The study employed a descriptive quantitative method involving 35 respondents selected as the research sample. The data analysis techniques included descriptive and inferential analyses, comprising simple linear regression, correlation and determination coefficient analyses, as well as hypothesis testing using SPSS version 25. The results indicate that motivation does not have a significant effect on employee performance. Meanwhile, work discipline is proven to have a positive and significant impact on employee performance at the Department of Agriculture of the Aru Islands Regency. These findings are supported by the statistical analyses conducted.